2020
DOI: 10.1186/s40900-020-00185-7
|View full text |Cite
|
Sign up to set email alerts
|

Between funder requirements and ‘jobbing scientists’: the evolution of patient and public involvement in a mental health biomedical research centre - a qualitative study

Abstract: Background: In the UK, there has been a strong drive towards patient and public involvement (PPI) in health research. Its benefits include improvements in the quality, relevance and acceptability of research, and empowerment, self-respect and value for service users. Organisational context can significantly influence the operationalisation of PPI. Research has highlighted power asymmetries between clinicians, researchers and service users. A resistance to power sharing, tokenism and assimilation into the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Madden and Speed's characterization of the operations of PPI as an ‘empty signifier’) 44 . Furthermore, our findings draw attention to the professionalization of researchers – an under‐examined issue in research on PPI, even as such research features extensive discussion of the liminal position of PPI contributors and the consequences of their potential professionalization 45‐48 . Indeed, the routine use of the term ‘researchers’ or ‘academics’ in PPI research obscures the complex professional power relations structuring academic work and applied research in particular – although some work on this is now emerging 49 .…”
Section: Discussion: From the Jigsaw To The Limpetmentioning
confidence: 74%
See 1 more Smart Citation
“…Madden and Speed's characterization of the operations of PPI as an ‘empty signifier’) 44 . Furthermore, our findings draw attention to the professionalization of researchers – an under‐examined issue in research on PPI, even as such research features extensive discussion of the liminal position of PPI contributors and the consequences of their potential professionalization 45‐48 . Indeed, the routine use of the term ‘researchers’ or ‘academics’ in PPI research obscures the complex professional power relations structuring academic work and applied research in particular – although some work on this is now emerging 49 .…”
Section: Discussion: From the Jigsaw To The Limpetmentioning
confidence: 74%
“…44 Furthermore, our findings draw attention to the professionalization of researchers -an under-examined issue in research on PPI, even as such research features extensive discussion of the liminal position of PPI contributors and the consequences of their potential professionalization. [45][46][47][48] Indeed, the routine use of the term 'researchers' or 'academics' in PPI research obscures the complex professional power relations structuring academic work and applied research in particular -although some work on this is now emerging. 49 In discussing the acculturation of the junior researcher, we show how meetings produce researcher identities by honing ECRs' institutional fluency through their engagement with technical apparatuses and absent/imagined actors.…”
Section: Discussion: From the J I G Saw To The Limpe Tmentioning
confidence: 99%
“…Similarly, a recent study of the development of public involvement in a London based mental health biomedical research centre reported that: “PPI remained localised and under resourced and there was a reluctance to change working practices which resulted in perceptions of tokenism. Service users faced conflicting expectations and were expected to assimilate rather than challenge the organisation’s ‘biomedical agenda’” [ 51 ] . …”
Section: How Public Involvement In Health Research Is Conceptualisedmentioning
confidence: 99%
“…Patient and public involvement is required for UK publicly funded health research, with researchers describing their involvement strategy. 2 , 3 Patient and public involvement is defined as ‘research carried out with or by members of the public rather than to, about or for them’, 4 where the public, patients and carers are active partners in research. 5 Traditional research models often confine patients to the end of the research ‘pipeline’, but ensuring collaboration across all stages can improve study outcomes, identify appropriate research questions and reduce ‘research waste’.…”
mentioning
confidence: 99%